Immunohistochemical Study of MDM2 Expression in Odontogenic Keratocyst and Dentigerous Cyst - Najmeh Jafari; Seyed Hoseein Tabatabaei; Fatemeh Kerdegari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2023)
Introduction: Dentigerous cyst and odontogenic keratocyst (OKC) are two of the most common developmental odontogenic cysts. Different developmental mechanism and biological behavior of OKC is due to unknown factors inherent in the epithelium or enzymatic activity in the wall. P53 plays a role in determining the pathways for DNA repair، apoptosis، angiogenesis and genomic stability and is negatively confronted with the MDM2 oncoprotein. Aim of this study was to evaluate the expression of MDM2 as an important indicator of proliferation and cell cycle regulation in OKC and dentigerous cyst. Methods: In this descriptive-cross-sectional study، MDM2 expression in the suprabasal and basal epithelium regions of 15 samples from each of the dentigerous cysts and OKC was assessed using immunohistochemistry. Finally، the data were entered into the SPSS16 software and analyzed using the t-test. Results: MDM2 expression in the suprabasal and basal epithelium regions in OKC was higher than dentigerous cyst، but there was not seen a statically significant difference (P: 0.551)، (P: 0.825). The expression level of this marker in both groups in the suprabasal region was significantly higher than the basal region (P: 0.005)، (P: 0.004). Conclusion: Higher expression of MDM2 in OKC، especially in the suprabasal areas، could indicate a secondary role of this protein in the pathogenesis، growth and spread of this cyst and the proliferation، apoptosis and differentiation processes confirm the neoplastic nature and specific biological behavior of this lesion.